Effects of bilateral transcranial direct current stimulation on working memory and global cognition in older patients with remitted major depression: A pilot randomized clinical trial. (21st July 2020) - Kumar, Sanjeev; Batist, Judah; Ghazala, Zaid; Zomorrodi, Reza M.; Brooks, Heather; Goodman, Michelle; Blumberger, Daniel M.; Daskalakis, Zafiris J.; Mulsant, Benoit H.; Rajji, Tarek K.
Abstract : Objectives: To assess the effects of a 10‐day course of bilateral anodal transcranial direct current stimulation (tDCS) of the dorsolateral prefrontal cortex (DLPFC) on working memory and global cognition in elderly participants with remitted major depressive disorder at 14 days (primary outcome) and 90 days (secondary outcome) post intervention. Design: Randomized double blind controlled trial (clinicaltrials.gov # NCT02212366). Setting: Community dwelling outpatient setting. Participants: Sixty or older with previous single or recurrent episodes of major depression currently in full remission. Intervention: A 10 day course of active or sham bilateral DLPFC anodal tDCS. Measurements: (a) Working memory assessed by a computerized N back task, and (b) global cognition assessed by a standard paper and pencil neuropsychological test battery. Results: Thirty‐three participants, (mean (SD) age = 66. 5 (5.7) year) were enrolled, out of which 18 (mean (SD) age = 66. 3 (5.8) year) were randomized to active tDCS and 15 (mean (SD) age = 66. 7 (5.8) years) to sham tDCS. All randomized participants except one from the sham group ‐completed the tDCS course. There were no differences between the groups on working memory performance or global cognition at 14 or 90 days post intervention. Both groups showed promising changes in working memory and global cognition over time. Conclusions: tDCS was well tolerated in older patients with remitted MDD, however, as compared to the sham group, it did not improve working memory or global cognition. Future studies should investigate tDCS with alternative parameters to enhance cognition in this population.